2020
DOI: 10.1111/1759-7714.13324
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐embedded cervical circular stapled anastomosis in esophagectomy

Abstract: Background Mechanical anastomosis is now widely used in surgery for esophageal cancer. An anastomotic fistula is still the most dangerous complication in mechanical anastomosis, especially for patients who undergo cervical anastomosis. However, due to the high anastomosis position and limited space, conventional embedding and suspension are rarely performed. This study aimed to introduce the steps of an improved embedded method in cervical circular stapled anastomosis and evaluate its efficacy in reducing comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Esophageal cancer is a high-incidence disease in the country. Currently, esophageal cancer is mainly treated by surgery, and although the effect is significant, complications such as postoperative anastomotic stenosis have always been a clinical problem [ 11 ]. Through investigation, it was found that 4 weeks after operation was a period of high incidence of anastomotic stenosis, 15% of patients were found to have anastomotic stenosis by endoscopy, and 42% of patients had swallowing function [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer is a high-incidence disease in the country. Currently, esophageal cancer is mainly treated by surgery, and although the effect is significant, complications such as postoperative anastomotic stenosis have always been a clinical problem [ 11 ]. Through investigation, it was found that 4 weeks after operation was a period of high incidence of anastomotic stenosis, 15% of patients were found to have anastomotic stenosis by endoscopy, and 42% of patients had swallowing function [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…While MIE is not yet seen as a standard procedure but becoming increasingly popular, mechanical anastomosis is already performed routinely in esophagectomy [ 6 ]. Mechanical anastomoses can be performed using linear stapling (LS) and circular stapling (CS) devices.…”
Section: Introductionmentioning
confidence: 99%
“…Anastomosis-related complications especially anasomotic leakage is one of the most lethal comorbidies, usually resulting in pyothorax, mediastinitis, tracheal fistula, arterial fistula or septicemia, and ending up with multiple organ failure eventually. In order to achieve satisfactory esophagogastric anastomosis, much effort had been tried either to optimize the anasomotic procedure (18,19,(30)(31)(32)(33)(34)(35)(36)(37), to better off the blood flow at the anastomotic site on the grafted conduits (11,38,39), or to manage prophylactic measurements to ensure the confinement of inflammation and facilitate the healing in case of leakage (20,21). In the present study we evaluated the utility of MOMA and compared it with CDHA in cervical esophagogastric anastomosis after sub-total esophagectomy in TE-SCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although efficacy of mechanical anastomosis had been reported previously ( 12 , 16 , 17 ), much effort had still been tried to better off the clinical outcome and simplify the procedure ( 18 , 19 ). Chen et al ( 20 ) reported that use of pleural flaps in the upper mediastinum would reduce the incidence of cervical subcutaneous emphysema and anastomotic leakage into pleural cavity.…”
Section: Introductionmentioning
confidence: 99%